Clinicopathological analysis of ovarian neoplasm - Samira Areen; Shahanaz Parvin; M. Nazmunnahar Mina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Ovarian neoplasm is a type of cancer caused by uncontrolled growth and division of cells within the ovary. It is a common type of gynecological cancer that affects a wide range of ages and can have various clinical, morphological, and histological features. This study aimed to examine the relationship between clinical presentation and histological pattern of ovarian neoplasm. Methods: This cross-sectional study conducted among 45 patients admitted to department of gynecology at Shaheed Suhrawardy medical college and hospital with features of ovarian neoplasm from February 2013 to February 2014. Results: The 82.3% of cases were benign tumors, 15.5% were malignant tumors, and 2.2% were borderline tumors. Benign tumors were more common in the 3rd decade, while malignant tumors were more common in the 4th to 6th decade. Symptoms of benign tumors included abdominal lumps and pain, while malignant tumors presented with abdominal pain, GIT-related symptoms, and ascites in some cases. The most common type of tumor was surface epithelial (84.5%), followed by germ cell (13.3%) and sex cord-stromal (2.2%) tumors. Conclusions: The study highlights the importance of recognizing the different clinical presentations of benign and malignant ovarian neoplasm.